Higher Education in Public Health as a Tool to Reduce Disparities: Findings from an Exploratory Study among the Bedouin Community in Israel - Osnat Bashkin; Avia Suisa; Sharon Levi (MDPI AG, 2023)
The Bedouin community is a minority disadvantaged population in Israel that suffers from a variety of health and socioeconomic disparities and limited access to higher education. The current study aimed to examine perceptions, successes, and challenges experienced by Bedouin students during their studies and to assess an internship program developed on the principles of a community-based participatory research approach to public health. In-depth interviews were conducted with 34 Bedouin students studying in the public health academic track between January and April 2023. Grounded Theory was used to analyze the data. Three main themes emerged from the analysis: (1) facilitators for the decision to pursue higher education in public health, (2) challenges and coping strategies, and (3) experiences of success. The internship program included eleven Bedouin students who conducted six community intervention projects covering a range of topics with different target Bedouin populations. Higher education is crucial for empowering minorities, producing leadership, and reducing socioeconomic and health gaps. The field internship enabled the necessary alignment between academia and public health practice. It is important to further reflect on the integration of minority groups in public health studies and its role in decreasing health inequity.